Problem and Project Based Learning in Hybrid Spaces: Nomads and Artisans - Ryberg, Thomas; Davidsen, Jacob; Hodgson, Vivien (Proceedings of the International Conference on Networked Learning, 2016)
There is a need within networked learning to understand and conceptualise the interplay between digital and physical spaces or what we could term hybrid spaces. Therefore, we discuss a recent study of students from two different programmes who are engaged in long-term, group-based problem and project based learning. Based on interviews, workshops and observations of students’ actual group practices in open, shared and flexible spaces in Aalborg University (AAU), we identify and discuss how students incorporate networked and digital technologies into their group work and into the study places they create for themselves. We describe how in one of the programmes ‘nomadic’ groups of students used different technologies and spaces for ‘placemaking’. We then show how their experience and approach to collaborative work differs to that of the more static or ‘artisan’ groups of students in the other programme. In both cases the ways of utilising space, places, tools and activities was an extremely complex interweaving of the digital and physical and of different places and artefacts over time. Thus, we argue ’placemaking’ is an important practice or literacy in relation to students’ ’doings of networked learning’ and one that impacts on the kind and nature of collaboration that takes place.